Microscale Biosignatures and Abiotic Mineral Authigenesis in Little Hot Creek, California - Kraus, Emily A.; Beeler, Scott R.; Mors, R. Agustin; Floyd, James G.; , GeoBiology 2016; Stamps, Blake W.; Nunn, Heather S.; Stevenson, Bradley S.; Johnson, Hope A.; Shapiro, Russell S.; Loyd, Sean J.; Spear, John R.; et al. (Frontiers in Microbiology, 2018)
Hot spring environments can create physical and chemical gradients favorable for unique microbial life. They can also include authigenic mineral precipitates that may preserve signs of biological activity on Earth and possibly other planets. The abiogenic or biogenic origins of such precipitates can be difficult to discern, therefore a better understanding of mineral formation processes is critical for the accurate interpretation of biosignatures from hot springs. Little Hot Creek (LHC) is a hot spring complex located in the Long Valley Caldera, California, that contains mineral precipitates composed of a carbonate base (largely submerged) topped by amorphous silica (largely emergent). The precipitates occur in close association with microbial mats and biofilms. Geological, geochemical, and microbiological data are consistent with mineral formation via degassing and evaporation rather than direct microbial involvement. However, the microfabric of the silica portion is stromatolitic in nature (i.e., wavy and finely laminated), suggesting that abiogenic mineralization has the potential to preserve textural biosignatures. Although geochemical and petrographic evidence suggests the calcite base was precipitated via abiogenic processes, endolithic microbial communities modified the structure of the calcite crystals, producing a textural biosignature. Our results reveal that even when mineral precipitation is largely abiogenic, the potential to preserve biosignatures in hot spring settings is high. The features found in the LHC structures may provide insight into the biogenicity of ancient Earth and extraterrestrial rocks.